Performance Comparison of Routing Protocols in Cognitive Radio Networks - Ranjita Joon, Parul Tomar (Mathematical Statistician and Engineering Applications, 2022)
Cognitive radio sensor networks (CRSNs) are the fifth-generation wireless sensor networks (WSNs). The growing demand of additional spectrum resources can be met by these networks. The cognitive radio technology eases the overcrowded unlicensed spectrum bands by providing an opportunity to use the unoccupied licensed spectrum bands. The lifetime of a wireless sensor network can be prolonged by clustering. Clustering involves selecting a cluster head and then rotating the cluster head periodically to distribute energy consumption among nodes in a cluster. The cluster heads collect the data from nodes in their cluster, aggregate it and send the data to the base station. There are a large number of protocols pertaining to CRSNs is available in the literature. This paper presents a comparative analysis of five routing protocols of CRSNs namely ECR (Energy and Cognitive Radio aware Routing), ERP (Energy aware event driven Routing), ESAC (Event driven Spectrum Aware Clustering), EACRP (Energy Aware Cluster based Routing Protocol) and SCR (Spectrum aware Cluster based Routing).